Users perception on the usefulness and ease of use of the enterprise resource planning system : a case study of JD Edwards financial suite in Sunway Technology Sdn. Bhd. / Azura Ahmad - Ahmad, Azura (2002)
This case study presents and discusses the user's perception on the usefulness and ease of use of an Enterprise Resource Planning (ERP) system of a selected organization. It is expected that the design feature of the system could contribute to the usage of the system by users (managers and executives) in performing their job task in their daily routine. Extensive literature review on the technology acceptance have been made. The objectives of this study are twofold. First, the study ranks the importance of the design feature placed by the respondents based on selected variables and characteristics of the system. Second, ERP system were correlated to the user's prior familiarity with the system. The study explores the association between these variables. The first findings on design feature revealed that the respondents had ranked variables such as content, system integration, mathematical accuracy, multi-level security, password security, processing option capability in their respective order of importance in term of usage. Visual attractiveness of the ERP system was not given high ranking by the users. On the question of "ease-of-use", the respondents had identified variables such as visual attractiveness, real-time integration and on-line function to have major influence on their perception of the system's capability in performing its task. In addition, the respondents have also perceived that the system's integration, data sequencing capability, programmed format checks, multi-level security and password security to influence them in terms of the usefulness of the system, In general, the respondents felt that they should be familiar with the system in order to improve their perceptions on the usefulness and ease of use of the system.